Ecclesiology and ethnography with humility: Going through Barth. (2nd January 2018) - Ward, Peter
Abstract : Drawing on the notion that future Ecclesiologies would be wise to go through Karl Barth rather than to attempt to go around him. This article proposes a cautious humility for ethnographic approaches to ecclesiology. The article builds on the move towards ethnographic forms of ecclesiology in a Scandinavian context. From this starting point it argues that Barth's ecclesiology suggests a series of theological checks and balances in ecclesiology and ethnography. These are explored through the notion of humility in method and approach.